Where do “chemical imbalance” beliefs come from? Evaluating the impact of different sources - Schroder, Hans S.; Tovey, Jordyn; Forer, Reni; Schultz, William; Kneeland, Elizabeth T.; Moser, Jason S. (Frontiers in Psychology, 2025)
IntroductionAlthough the etiology of depression is incredibly complex, the narrative that it is caused by a simple “chemical imbalance” persists in lay settings. We sought to understand where people are exposed to this explanation (i.e., the “source”), and the relative influence of each source.MethodsA total of 1,219 college students were asked where they had heard of the chemical imbalance explanation and how much they believed this to be true. Independent raters coded open-ended responses and we used self-report measures to capture chemical imbalance belief endorsement.ResultsThe most common sources of exposure to this explanation were the classroom, the Internet/media, other people (e.g., friends), and healthcare providers. In a regression analysis, only learning about the chemical imbalance explanation from healthcare providers uniquely predicted the adoption of the chemical imbalance belief. The correlation held even after controlling for depression symptoms, a family history of depression, and having had a diagnosis or treatment of mental health disorder (all of which also uniquely predicted chemical imbalance belief endorsement).DiscussionThese results suggest that healthcare providers play an important role in the dissemination of the chemical imbalance message, which is an oversimplified, scientifically controversial, and potentially treatment-interfering narrative. Interventions directed at healthcare providers may help them engage with more accurate messages.